Soft Computing Applications Proceedings of the 5th International Workshop Soft Computing Applications (SOFA) - Balas, Valentina Emilia.; Fodor, Jǹos.; Vr̀konyi-Kc̤zy, Annamr̀ia R.; Dombi, Joszef.; Jain, Lakhmi C. (Advances in Intelligent Systems and Computing,, 2013)
This volume contains the Proceedings of the 5thInternational Workshop on Soft Computing Applications (SOFA 2012). The book covers a broad spectrum of soft computing techniques, theoretical and practical applications employing knowledge and intelligence to find solutions for world industrial, economic and medical problems. The combination of such intelligent systems tools and a large number of applications introduce a need for a synergy of scientific and technological disciplines in order to show the great potential of Soft Computing in all domains. The conference papers included in these proceedings, published post conference, were grouped into the following area of research: ʺ Soft Computing and Fusion Algorithms in Biometrics, ʺ Fuzzy Theory, Control andApplications, ʺ Modelling and Control Applications, ʺ Steps towards Intelligent Circuits, ʺ Knowledge-Based Technologies for Web Applications, Cloud Computing and Security Algorithms, ʺ Computational Intelligence for Biomedical Applications, ʺ Neural Networks and Applications, ʺ Intelligent Systems for Image Processing, ʺ Knowledge Management for Business Process and Enterprise Modelling. The combination of intelligent systems tools and a large number of applications introduce a need for a synergy of scientific and technological disciplines in order to show the great potential of Soft Computing in all domains.